Exploring algorithmic bias in cybersecurity : the social implications of AI-driven threat detection and risk scoring - Moabi, Boitshwarelo Precious (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.